Pengaruh Good Corporate Governance, Profitabilitas, dan Size terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan-perusahaan LQ45 di Bursa Efek Indonesia) - Fuady, Misbach; Hidayat, Riskin; Rosita, Rosita; Susanto, Heri (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to examine the effect of good corporate governance, profitability and company size on company value in the most actively traded companies on the IDX in the period 2015-2019. The population used in this study were companies included in the LQ 45 index listed on the IDX during that period. The sample selection technique used purposive sampling, while the data analysis technique used multiple linear regression analysis. The results of this study indicate that institutional ownership and profitability have a significant positive effect on company value. The proportion of the board of commissioners has a significant negative effect on company value and company size has a significant negative effect on company value. The Adjusted R2 value of 0.482 indicates that 48.2% of the variation in company value can be explained by variations in the four independent variables, namely institutional ownership, proportion of the board of commissioners, profitability and company size. While the remaining 51.8% is explained by other causes not examined in this study